Baseline [123I]FP‐CIT SPECT (DaTSCAN) severity correlates with medication use at 3 years in Parkinson's disease. (20th August 2013) - Nissen, T.; Malek, N.; Grosset, K. A.; Newman, E. J.; Patterson, J.; Hadley, D.; Grosset, D. G.
<x xml:space="preserve">Abstract</x> Background Presynaptic dopaminergic deficiency on dopamine transporter imaging supports a clinical diagnosis of Parkinson's disease and correlates with the severity of rigidity and bradykinesia. Baseline dopaminergic deficiency predicts clinical severity, but the relationship with subsequent medication use has not been reported. Methods A randomly selected cross section of 83 Parkinson's disease (PD) patients who had [123I] FP‐CIT SPECT at the time of clinical diagnosis was identified. Dopaminergic deficiency was graded 1, 2 or 3 with increasing severity using visual assessment and by semiquantitative analysis of putamen and caudate uptake. Antiparkinson medication usage and clinical severity by Hoehn and Yahr were noted annually to 3 years. Results In 83 patients (66% male, median age 65.0 years, IQ 55.4–71.8), [123I]FP‐CIT SPECT was grade 1 in 20 (24%), grade 2 in 53 (64%) and grade 3 in 10 patients (12%). Dopamine transporter uptake ratios were inversely associated with antiparkinson medication usage (r = −0.26, P = 0.0201) and Hoehn Yahr stage (r = −0.32, P = 0.0029) at 3 years from baseline, but there was considerable variation in drug usage in individual patients. At 3 years, patients with grade 1 scans at baseline received a median dose of 325 levodopa equivalent units (LEU) (interquartile range 175–433); grade 2 scan patients 400 LEU (interquartile range 300–635); and grade 3 scan patients 460 LEU (interquartile range 252–658). Conclusion The degree of reduction in presynaptic dopaminergic uptake at baseline is associated with higher antiparkinson drug dosage at follow‐up, but the wide variation means that the baseline FP‐CIT SPECT does not reliably predict drug use in individual cases.